Is abstention an escape from Arrow's theorem? - Cengelci, Murat Ali; Sanver, M. Remzi (Springer, 2007)
In a society of variable size, Quesada (Soc Choice Welfare 25(1): 221-226, 2005) establishes the existence of Arrovian social welfare functions which are not dictatorial. We show that this escape from the Arrovian impossibility collapses when a very mild monotonicity condition is introduced.
Keywords: Majority-Rule; Societies; Profiles